White-Water Rafting Tourism: Questioning the Role of Destination Image, Destination Personality, Novelty-Seeking, and Perceived Value in Determining Visit Intention - Suhud, Usep; Allan, Mamoon; Rahmawaty, Penny; Juliana, Juliana; Berutu, Meta Bara (Journal of Ecohumanism, 2025)
A plethora of tourist behaviour studies have investigated white-water rafting in the existing literature. However, the factors that cause visit intention used in this study still need to be found. For this reason, this study examines the effect of destination image, novelty-seeking, and perceived value on visit intention. The destination of white-water rafting is a river with a certain level of hardness and route length, as offered by the organizers. There were 224 participants, and they were selected using the convenient sampling method. Data analysis used exploratory factor analysis and structural equation models. This study found a significant effect of destination image on novelty-seeking and perceived value. In addition, novelty-seeking significantly affected visit intention and perceived value, whilst perceived value substantially influences visit intention.